(untitled) (Veterinária Notícias, 2022)
The lupus erythematosus complex is an immune-mediated dermatological disease, being mainly represented by the generalized and discoid form. The latter described is milder, as it is limited to the appearance of lesions, usually on the face and in mucocutaneous regions. Its pathophysiology is considered multifactorial, however, continuous exposure to ultraviolet radiation seems to be very relevant to trigger and / or aggravate clinical manifestations. The definitive diagnosis is obtained by histopathological analysis, and the treatment is based mainly on immunosuppression and protection against ultraviolet radiation. The objective of this study was to report the case and clinical evolution of a mixed breed dog, diagnosed with discoid lupus erythematosus, in addition to addressing the risks, benefits and need to institute continuous therapy to control this disorder. Therapeutic success can vary between patients, since the intensity of the disease can be manifested in varying degrees. Therefore, in those individuals where the condition is mild, it may be advantageous to opt for more conservative therapies, in order to avoid their side effects.